Analysis of Service Satisfaction Level at Batam Center International Port in Batam City Using the Fuzzy Mamdani Method - Candra, Joni Eka; Permatasari, Ririt Dwiputri; Hazimah, Hazimah (Politeknik Ganesha Medan, 2024)
A port is defined as a facility and system where a port is a work environment consisting of a land and water area equipped with berthing and mooring facilities for ships, a place for loading and unloading, and boarding and disembarking passengers from one mode of sea transportation to another mode of transportation. In carrying out activities at the port, apart from providing sufficient facilities and equipment, quality services cannot be neglected. This research aims to analyze and determine how much influence the level of service provided has on the satisfaction response of ship passengers at the Batam Center International Port, Batam City. To carry out this research, the study used a literature review, observation, and distribution of questionnaires using a Likert scale and the Fuzzy Mamdani method. However, several challenges were encountered during the study. First, there was a difficulty in obtaining a representative sample of passengers due to the variability in passenger traffic and schedules. Second, the subjective nature of satisfaction measurement posed challenges in ensuring the accuracy and consistency of responses. Third, integrating the qualitative data from the Likert scale with the quantitative Fuzzy Mamdani method required careful handling to avoid misinterpretation The expected results from this research are the levels of satisfaction ship passengers feel regarding the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. This will help determine whether passengers perceive themselves as satisfied or dissatisfied. Based on the analysis and discussion carried out with 50 respondents using the Likert scale method, the respondents stated that they were quite satisfied. This indicates that the Batam Center International Port, Batam City, is quite successful in providing satisfactory services to passengers. From the dimensions of reliability, responsiveness, assurance, empathy, and tangibles, overall consumers feel quite satisfied, with an average satisfaction percentage of 71% (35.5 out of 50 respondents). Similarly, the results obtained from the Fuzzy Logic Mamdani method show an output value for consumer satisfaction of 150 (within a range of 50–250), indicating that the level of consumer satisfaction with the services provided by the Batam Center International Port, Batam City, is quite satisfactory